(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article provides the analyses of Vasily Simovych’s research of the Ukrainian spelling and the History of the reform Ukrainian spelling, main directions of research of the Ukrainian spelling.